2021
DOI: 10.3389/fnbot.2020.607455
|View full text |Cite
|
Sign up to set email alerts
|

Sprawling Quadruped Robot Driven by Decentralized Control With Cross-Coupled Sensory Feedback Between Legs and Trunk

Abstract: Quadruped animals achieve agile and highly adaptive locomotion owing to the coordination between their legs and other body parts, such as the trunk, head, and tail, that is, body–limb coordination. This study aims to understand the sensorimotor control underlying body–limb coordination. To this end, we adopted sprawling locomotion in vertebrate animals as a model behavior. This is a quadruped walking gait with lateral body bending used by many amphibians and lizards. Our previous simulation study demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Suzuki et al reported that a walk is generated by feedback of the joint torque to the CPG, and that the speed increased and the energy consumption improved [48]. We have achieved similar results in our previous work [32], which demonstrated that when the gait transitioned from a trot to a gallop, the speed increased sharply and the energy consumption decreased.…”
Section: Related Worksupporting
confidence: 85%
“…Suzuki et al reported that a walk is generated by feedback of the joint torque to the CPG, and that the speed increased and the energy consumption improved [48]. We have achieved similar results in our previous work [32], which demonstrated that when the gait transitioned from a trot to a gallop, the speed increased sharply and the energy consumption decreased.…”
Section: Related Worksupporting
confidence: 85%
“…Each trial was conducted on flat terrain for 60 s, with the oscillator phases initially set to random. The body size and weight were determined by considering those of a salamander robot developed as a prototype in our previous study (Suzuki et al 2019b). The angular frequency and amplitude of the legs were chosen with physically plausible values.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The interactions of the sensory feedback from body to limb and limb to body establish the relationship between the legs and trunk, providing longer strides and more powerful pushing-off against the ground. The interactions of the body-to-limb and limb-to-body feedback establish the relationship between the legs and trunk, providing longer strides and more powerful pushing-off against the ground (Suzuki et al, 2019(Suzuki et al, , 2021. Equation ( 7) relates to the body-to-body feedback.…”
Section: Body Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches bring us a neat use of CPGs in order to control a sprawling quadruped robot (Suzuki et al, 2021), contributing to decentralized control with cross-couple sensory feedback to shaping body-limb coordination, which differs from previous research based on CPGs that works with inter-oscillator couplings or gait patterns based on geometric mechanics. Ngamkajornwiwat et al (2020) propose an online self-adaptive locomotion control technique based on the integration of a modular neural locomotion control (MNCL) and an artificial hormone mechanism (AHM) for a walking hexapod robot.…”
Section: Introductionmentioning
confidence: 99%